SURVIVAL AND GROWTH RATES OF TRANSPLANTED SCLERACTINIAN CORALS ON THE REEF FLAT AT KALASEI WATERS, MINAHASA REGENCY, NORTH SULAWESI - Tioho, Hanny; Paruntu, Carolus P; Patrich, Hendra (Graduate Program of Sam Ratulangi University, 2013)
In order to know survival and growth rates of some scleractinian coral species, 538 colonies from 46 species were collected from the reef which was affected by reclamation activity and transferred to the adjacent reef about 300 meters from the former location. All of the transplanted colonies were observed during 12 months (April 2011 ? March 2012). We found that 47 (8.74%) dead coral colonies dominated by branching corals and 491 (91.26%) were dominated by live coral colonies of the growth forms encrusting, folioseandmassive. The highest coral growth (10.59 to 11.32cm/year) was showed by branching Acropora, while the lowest (0.35 to 0.71 cm/year ) was showed by the group of massive-submassive growth form. This study concluded that corals with encrusting, folioseandmassive growth formhad a high survival rate, but they have slow growth ratescompared withbranching growth form. Untuk mengetahui tingkat ketahanan hidup dan pertumbuhan karang Scleractinia, 46 jenis karang Scleractinia yang terdiri dari 538 koloni dikoleksi dari areal terumbu karang yang sementara direklamasi dan ditransplantasi ke area rataan terumbu yang berjarak sekitar 300 meter dari area aktivitas reklamasi di pantai Kalasey dan pengamatan dilakukan selama satu tahun (April 2011 - Maret 2012). Ditemukan 47 (8,74 %) koloni karang yang mati dan didominasi oleh karang bercabang, dan 491 (91,26 %) koloni yang hidup didominasi oleh karang dengan bentuk pertumbuhan encrusting, foliose dan massive. Pertumbuhan karang tertinggi adalah karang bercabang dari kelompok Acropora yaitu 10,59 - 11,32 cm/Tahun, sedangkan terendah adalah kelompok dengan bentuk pertumbuhan massive-submassive yaitu 0,35 - 0,71 cm/Tahun. Penelitian ini memperlihatkan bahwa karang dengan bentuk pertumbuhan encrusting, foliose dan massive memiliki tingkat ketahanan hidup yang lebih tinggi, tetapi memiliki pertumbuhan yang lebih lambat dibandingkan dengan karang bercabang.